The diagnostic role of fat in osteosarcopenia - Al Saedi, Ahmed; Hassan, Ebrahim Bani; Duque, Gustavo (Journal of Laboratory and Precision Medicine; Vol 4 (February 2019): Journal of Laboratory and Precision Medicine, 2019)
Osteosarcopenia is a newly defined geriatric syndrome with serious consequences in the older population. Therefore, early identification of this syndrome and accurate prediction of poor outcomes and response to treatment are crucial. However, the diagnostic methods for sarcopenia and osteoporosis have several limitations. In this review, we briefly discuss the pathogenesis of osteosarcopenia in the light of new discoveries on the importance of local lipotoxicity induced by intramuscular and marrow fat. We also discuss the current and possible future diagnostic methods for osteosarcopenia focusing on the identification and quantification of tissue-embedded fat.